2015
DOI: 10.1155/2015/582462
|View full text |Cite
|
Sign up to set email alerts
|

Severe Impaction of the Primary Mandibular Second Molar Accompanied by Displacement of the Permanent Second Premolar

Abstract: Tooth impaction is defined as any tooth that fails to erupt into a normal functional position and remains unerupted beyond the time at which it should normally erupt. Reports of impaction and eruption failure in primary teeth are relatively rare compared to permanent teeth. We report 2 rare cases where the second premolar was located on the occlusal side of the impacted mandibular second primary molar. In the first case, the succedaneous permanent tooth erupted after extraction of the primary tooth, fenestrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 6 publications
0
10
1
5
Order By: Relevance
“…When the exfoliation of ankylosed teeth is late, problems like deviated eruption paths for nearby and opposing teeth, delayed eruption of succedaneous permanent teeth and also the position of the tooth germ can be affected leading to hooked roots. 2,7 For the management of patient with submerged teeth, the conservative treatment option was composite build-up or a stainless-steel crown to prevent tipping of adjacent teeth and to bring back the occlusion to the position, thus prevents opposing arch tooth from supra-eruption. However, because the infra-occlusion was severe in this case, it is not possible to build-up of the occlusal table with composite resin or stainless-steel crown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the exfoliation of ankylosed teeth is late, problems like deviated eruption paths for nearby and opposing teeth, delayed eruption of succedaneous permanent teeth and also the position of the tooth germ can be affected leading to hooked roots. 2,7 For the management of patient with submerged teeth, the conservative treatment option was composite build-up or a stainless-steel crown to prevent tipping of adjacent teeth and to bring back the occlusion to the position, thus prevents opposing arch tooth from supra-eruption. However, because the infra-occlusion was severe in this case, it is not possible to build-up of the occlusal table with composite resin or stainless-steel crown.…”
Section: Discussionmentioning
confidence: 99%
“…Al Hassan Ali Owis 1 , Zarah Ahmed Dahas 2 , Omar Dharaj 3 , Turki Abduh Khurayzi 4 , Fareedi Mukram Ali 5 1 Dental Intern, College of Dentistry, Jazan, Kingdom of Saudi Arabia. 2 Dental Intern, College of Dentistry, Jazan, Kingdom of Saudi Arabia. 3 Dental Intern, College of Dentistry, Jazan, Kingdom of Saudi Arabia.…”
Section: Submerged and Impacted Deciduous Molars In 27-year-old Male mentioning
confidence: 99%
See 1 more Smart Citation
“…Inversion of the intraosseous positions of the primary molar and its succedaneous premolar is a very rare phenomenon [3]. Kjaer et al [4] stu died 29 cases of arrested eruption of primary molars and found 4 premolars to be located occlusal to the Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Süt dişlerinin ankilozu sıklıkla bu dişlerin gömülü kalmasına neden olarak gösterilmektedir 22 . Travma, periodontal ligamentte yaralanma, konjenital olarak daimi diş eksikliği, dentigeröz kist, daimi diş germinin anomalisi, periodontal membranda defekt, erken süren daimi birinci molar, hatalı sürme kuvvetleri ya da bu faktörlerin kombinasyonları da etken olarak gösterilebilmektedir [23][24] . Ayrıca odontoma benzeri sert doku anomalileri, miksofibröz hiperplazi ve ameloblastik fibroma gibi yumuşak doku değişiklikleri ile sürme yolunun mekanik olarak engellenmesi veya o bölgedeki sinir aktivitesinde meydana gelen geçici değişiklikler gibi kazanılmış nedenler süt dişlerinin gömülü kalma potansiyelini arttıran nedenler arasında gösterilmektedir 22 .…”
Section: Olgu 4 (Odontomaya Bağlı Persiste Süt Dişi)unclassified